2016
DOI: 10.1016/j.pep.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of KEX1 gene reduces the proteolytic degradation of secreted two-chain Insulin glargine in Pichia pastoris

Abstract: a b s t r a c tInsulin glargine is a slow acting analog of insulin used in diabetes therapy. It is produced by recombinant DNA technology in different hosts namely E. coli and Pichia pastoris. In our previous study, we have described the secretion of fully folded two-chain Insulin glargine into the medium by over-expression of Kex2 protease. The enhanced levels of the Kex2 protease was responsible for the processing of the glargine precursor with in the host. Apart from the two-chain glargine product we observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Boehm et al[257] developed a kex1 mutant of P. pastoris, which prevented the removal of the C-terminal lysine of endostatin, at least in fermentations up to 40 h. It was speculated that degradation observed in longer runs was caused by carboxypeptidase Y released through cell lysis. Later studies also showed reduced degradation in P. pastoris kex1 strains of hirudin[272] and insulin glargine[273]. The degradation of hirudin in wild-type P. pastoris resembled the atypical Kex1 cleavage observed by Heim et al[271] in S. cerevisiae, in that the nonbasic C-terminal residues Gln65 and Leu64 (and Tyr 63 ) were removed[272].…”
mentioning
confidence: 65%
“…Boehm et al[257] developed a kex1 mutant of P. pastoris, which prevented the removal of the C-terminal lysine of endostatin, at least in fermentations up to 40 h. It was speculated that degradation observed in longer runs was caused by carboxypeptidase Y released through cell lysis. Later studies also showed reduced degradation in P. pastoris kex1 strains of hirudin[272] and insulin glargine[273]. The degradation of hirudin in wild-type P. pastoris resembled the atypical Kex1 cleavage observed by Heim et al[271] in S. cerevisiae, in that the nonbasic C-terminal residues Gln65 and Leu64 (and Tyr 63 ) were removed[272].…”
mentioning
confidence: 65%